Analisis Dan Perancangan Sistem Informasi Manajemen Anggaran Pada Badan Perencanaan Pembangunan Daerah Provinsi Jambi - Suherdiansyah, Febri; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
BAPPEDA has the task of assisting the Governor in carrying out some regional government affairs in thearea of regional development planning based on the applicable laws and regulations. a) The JambiProvincial Regional Development Planning Agency carries out functions: formulating technical policiesfor regional development planning; b) coordinating the preparation of regional development planning; c)fostering the implementation of tasks in the area of regional development planning; d) implementation ofregional development control and evaluation; and e) other functions performed by the Governor inaccordance with their duties and functions. In carrying out its functions, BAPPEDA is inseparable fromthe problems, namely a) Inconsistent planning and budgeting, among planning documents such as theabsence of programs in the Jambi Provincial Medium-Term Development Plan (RPJMD). b) Does notmatch program name in Jambi Province RPJMD. c) There are no activities in the Strategic Plan(RENSTRA). d) Does not match the target activities that have been set in the Strategic Plan. From theseproblems the writer tries to design a budget management information system using the Unified ModelingLanguage (UML) system modeling and the results are in the form of a prototype system design. Thisresearch resulted in a prototype of the Budget Management Information System design at BadanPerencanaan Pembangunan Daerah (BAPPEDA) Jambi Provincial. With the design of the BudgetManagement Information System it is expected to be the basis for solving problems that occur at BadanPerencanaan Pembangunan Daerah (BAPPEDA) Jambi Provincial. In this research, it is expected thatBAPPEDA can measure the realization of outputs of activities against planned plans and can monitor theachievement of activity outputs.